2019
DOI: 10.1021/acsomega.9b02231
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Safety Assessments of Industrial Production of Levulinic Acid via Acid-Catalyzed Dehydration

Abstract: These days, there is a need to develop novel and emerging processing pathways that permit production of value-added substances and fuels considering sustainability aspects. In this sense, levulinic acid (LA) is one of the most promising biorefinery products. This paper presents environmental and safety assessments of LA production via acid-catalyzed dehydration (ACD) of biomass. The process was modeled by using Aspen Plus process simulation software based on a capacity of 132 000 tons per annum of banana rachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…We selected natural gas as the base energy source, considering the recommendation of previous studies for analogous topologies. 38 Figure 2 displays the obtained PEI rates based on the proposed scenarios on time and mass of product basis. In Figure 2 , I gen refers to the generation rate, while I out is the output rate.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected natural gas as the base energy source, considering the recommendation of previous studies for analogous topologies. 38 Figure 2 displays the obtained PEI rates based on the proposed scenarios on time and mass of product basis. In Figure 2 , I gen refers to the generation rate, while I out is the output rate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, the evaluation of the process safety of emerging and green-based technologies has attracted much interest regarding the sustainability of the plants. Meramo-Hurtado et al 38 used inherent safety (and environmental) analysis along with computer-aided process engineering to evaluate and diagnose an industrial synthesis of levulinic acid via acid-catalyzed dehydration, as a strategy for crop waste valorization. A crude palm oil process was examined by Moreno-Sader et al, 39 implementing hazard/risk identification and environmental evaluation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, was found that in the process is handled large amounts of mass that represent a stressed factor for the safety of the plant; therefore, the most critical and risky operational variable is the inventory. Comparing the results with those obtained for the inherent safety analysis of a levulinic acid production process via acid-catalyzed (I = 24) [37] and a bioethanol production process (I = 23) [38], it is found that the process under study has a lower safety performance. Although substances of equal risk potential such as ethanol are involved and exothermic reactions are performed, these two processes handle lower inventories.…”
Section: Inherent Safety Analysismentioning
confidence: 98%
“…Also, the operational pressure was kept at atmospheric conditions (101.32 kPa), which represents no risk to the process. The inventory subindex measures the mass contained in any process equipment ( tanks, reactors, mixers, and others) for a hydraulic retention time of 1 h [37]. A total inventory of 1,500 tones was calculated for the inside battery limits (ISBL); the outside battery limits (OSBL) were not considered in the inventory calculation due to the main processing units belongs to ISBL.…”
Section: Inherent Safety Analysismentioning
confidence: 99%
See 1 more Smart Citation